1988
DOI: 10.1007/bf01940542
|View full text |Cite
|
Sign up to set email alerts
|

Distal axonopathy in streptozotocin diabetes in rats

Abstract: We noted the earliest morphological changes in the motor endplates 8 weeks after the induction of streptozotocin diabetes in rats. Morphometric measurements showed reduced axonal areas of the lateral plantar and the sciatic nerves in the diabetic rats 28 but not 2 and 8 weeks after the experiment. These findings suggested distal axonopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
6
1
1
Order By: Relevance
“…Although most of the previous studies have described alterations of distal muscles (Feczko and Klueber, 1988;Chokroverty et al, 1988;Cotter et al, 1989;Klueber et al, 19891, our results suggest that experimental diabetes also produces structural alterations in proximal skeletal muscle. In addition to the existence of type I1 myofiber atrophy, the appearance of type IIC fibers without degenerative changes in the diabetic rectus femoris suggests a possible muscle denervation (Sunderland, 1985).…”
Section: Discussioncontrasting
confidence: 70%
“…Although most of the previous studies have described alterations of distal muscles (Feczko and Klueber, 1988;Chokroverty et al, 1988;Cotter et al, 1989;Klueber et al, 19891, our results suggest that experimental diabetes also produces structural alterations in proximal skeletal muscle. In addition to the existence of type I1 myofiber atrophy, the appearance of type IIC fibers without degenerative changes in the diabetic rectus femoris suggests a possible muscle denervation (Sunderland, 1985).…”
Section: Discussioncontrasting
confidence: 70%
“…Metabolic changes in nerve vasculature, with resulting decrease in nerve blood flow and endoneurial hypoxia, have a key role in nerve conduction slowing in short-term diabetes [4, 15±20]. Metabolic imbalances in the neural tissues, closely associated with impaired neurotrophism [13, 25±27, 33] and neurotransmission [34±36], contribute to Schwann cell injury [37,38] and axonopathy [39,40]. These abnormalities which develop gradually and become manifest in long-standing diabetes [38,39] exacerbate nerve functional deficits acquired in the initial phase of diabetic neuropathy.…”
mentioning
confidence: 99%
“…Metabolic imbalances in the neural tissues, closely associated with impaired neurotrophism [13, 25±27, 33] and neurotransmission [34±36], contribute to Schwann cell injury [37,38] and axonopathy [39,40]. These abnormalities which develop gradually and become manifest in long-standing diabetes [38,39] exacerbate nerve functional deficits acquired in the initial phase of diabetic neuropathy. The importance of sorbitol pathway-linked metabolic imbalances in neural structures is illustrated by findings [41] of a large increase in neuroaxonal dystrophy with SDH inhibition by the dose of SDI not affecting nerve blood flow in the diabetic model of lesser duration [4].…”
mentioning
confidence: 99%
“…Britland et al (1985) and Bhoyrul et al (1988) showed a reduction of the myelinated axonal area in the sciatic and tibial nerves of SZT-diabetic rats while Sharma et al (1985), McCallum et al (1986) 58 axonal caliber in the tibial and sural nerves of STZ-diabetic rats. The investigation of distal (plantar) nerves confirmed the axonal atrophy (Brown et al, 1980;Sharma et al, 1981;Chokroverty et al, 1988;Thomas et al, 1990) present in this experimental model of diabetic neuropathy. These findings added the information of a "dying back" neuropathy with breakdown of myelinated fibers in the most distal nerves with preservation of the fibers in more proximal ones (Brown et al).…”
mentioning
confidence: 68%